ASEAN‐5 bond market development: Where does it stand? Where is it going?. (May 2014) - Felman, Joshua; Gray, Simon; Goswami, Mangal; Jobst, Andreas A.; Pradhan, Mahmood; Peiris, Shanaka; Seneviratne, Dulani
<x xml:space="preserve">Abstract</x> Since the late 1990s' Asian crisis, ASEAN‐5 countries have expended considerable effort in developing their bond markets. However, the size of these markets relative to GDP has hardly changed. Can we explain this? And does it mean that domestic markets have not, in fact, developed? The article argues that bond market growth has been held back by a sharp fall in business investment, which has left firms with little need for bond borrowing. Even so, markets have developed in other ways, to such an extent that substantial amounts of foreign portfolio investment have begun to flow into ASEAN‐5 bonds. These developments have important ramifications. With the investor base growing and infrastructure investment likely to rise, ASEAN‐5 bond markets could expand rapidly, holding out the prospect that the region could finally achieve 'twin engine' financial systems in the near future.